Management of nursing care for athletes with musculoskeletal injuries: An experience of Specialized Care Centers in Traumatology and Orthopedics (Research, Society and Development, 2022)
Objective: To report the experience of nursing care for athletes with musculoskeletal injuries in Specialized Care Centers (CAE) in Traumatology and Orthopedics. Methodology: Descriptive study in the experience report modality regarding nursing care for athletes with musculoskeletal injuries, developed from 2017 to 2020, at the Specialized Care Centers in Traumatology and Orthopedics of a federal public hospital, in high complexity care, from the municipality of Rio de Janeiro. Result: Nurse care in Specialized Care Centers re-signifies the assistance provided to athletes with musculoskeletal injuries, contributing to reduce kinesiophobia and their return to sports activities. The flow of care advocates the nurse as a reference in the care of this clientele, favoring the interrelationship between athlete-family-professional. Conclusion: The care in the patient-centered management model, defended by the CAEs, represents a differential in the integral follow-up that begins with the entry into the health institution until the end of the treatment, making it possible to promote health, rehabilitate injuries and facilitate the return to sports with greater confidence involving the athlete and the family in decision making.